Association Between Preinfarction Angina and Culprit Lesion Morphology in Patients With ST-Segment Elevation Myocardial Infarction: An Optical Coherence Tomography Study - Wang, Ying; Sheng, Zhaoxue; Li, Jiannan; Tan, Yu; Zhou, Peng; Liu, Chen; Zhao, Xiaoxiao; Zhou, Jinying; Chen, Runzhen; Song, Li; Zhao, Hanjun; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies reported the cardiac protection effect of pre-infarction angina (PIA) in patients with acute myocardial infarction (AMI). We sought to identify culprit-plaque morphology and clinical outcomes associated with PIA in patients with ST-segment elevation myocardial infarction (STEMI) using optical coherence tomography (OCT). Method and Results: A total of 279 STEMI patients between March 2017 and March 2019 who underwent intravascular OCT of culprit-lesion were included. Of them, 153 (54.8%) presented with PIA. No differences were observed in clinical and angiographic data between two groups, except STEMI onset with exertion was significantly less common in PIA group (24.2% versus 40.5%, P = 0.004). Patients with PIA exhibited a significantly lower incidence of plaque rupture (40.5% versus 61.9%, P < 0.001) and lipid-rich plaques (48.4% versus 69.0%, P = 0.001). The thin-cap fibroatheroma (TCFA) prevalence was lower in PIA group, presenting a thicker fibrous cap thickness, although statistically significant differences were not observed (20.3% versus 30.2%, P = 0.070; 129.1 ± 92.0μm versus 111.4 ± 78.1μm, P = 0.088; respectively). Multivariate logistic regression analysis indicated that PIA was an independent negative predictor for plaque rupture (odds ratio: 0.44, 95% confidence interval: 0.268-0.725, P = 0.001). No significant differences in clinical outcomes were observed besides unplanned revascularization. Conclusion: Compared with non-PIA group, STEMI patients with PIA showed a significantly lower prevalence of plaque rupture and lipid-rich plaques in culprit-lesion, implying different mechanisms of STEMI attack in these two groups.